Synthesis and Antifungal Activity of N4-(Piperazinoyl-methyl)- N,N-diaryl-2-(3-oxo-1,4-benzothiazin-2-yl)acetamide - Goel, K.K.; Nagori, B.P.; Gupta, G.; Goel, N.; Patil, S.; Gajbhiye, A. (Asian Journal of Chemistry, 2013)
A series of N4-(piperazinoyl-methyl)-N,N-diaryl-2-(3-oxo-1,4- benzothiazin-2-yl) acetamide have been synthesized by the condensation of the N,N-diaryl-2-(3-oxo-1,4-benzothiazin-2-yl) acetamide with chloroacetic acid and then with piperazine. All the synthesized compounds have been tested for their antifungal activity against Tricophyton rubrum, Epidermophyton floccosum and Malassazia furfur. Some of the compounds exhibited appreciable activity. The structure of the synthesized compounds 7a-c has been established on the basis of elemental analysis and spectral data.